Efficacy of Guduchyadi Kwatha Yoni Prakshalana on Acharana Yonivyapad (AYUSHDHARA, 2024)
Acharana Yonivyapada is related to inflammatory conditions of reproductive system. On reviewing its features it can be possibly considered as Vulvovaginitis. Vulvovaginitis is defined as infections of vulva and vagina causing vulvar and vaginal itching, burning sensation, irritation and vaginal discharges of various types. Present study was framed to establish an Ayurvedic way of management to vulvovaginitis requiring minimal hospital visits. Considering the prevalence of this disease, we have planned this study and selected Guduchyadi Kwatha Yoni Prakshalana as Sthanika chikitsa.